Effect of Planting Media and Varieties on Growth and Yield Production of Shallots (Allium cepa L.) - Al Machfudz WDP; Deni Hari Prasetyo (Nabatia, 2021)
This study aims to determine the effect of planting media and varieties on the growth and yield of shallot (Allium cepa L.) It was conducted from January to March 2020. The study used a randomized block design with 2 factors. Factor 1 is the type of planting media, namely without manure, chicken manure 10 tons/ha, goat manure 10 tons/ha, cow manure 10 tons/ha. Factor 2 is the shallot varieties Keta Monca and the Philippines. The results showed that there was an interaction between planting media and onion varieties on plant length variables in the combination of goat manure media with Filipino varieties at the age of 21 days with the highest yield (23,700 cm), while at 28 days it occurred in the combination of chicken manure media with keta varieties. monca with the highest yield (29,889 cm). In the variable number of leaves there was an interaction between chicken manure media and keta monca varieties at the age of 21 days (23.778 strands) and at the age of 28 days (28,000 pieces). plant, tuber wet weight per plant, tuber wet weight per plot, tuber dry weight per plant and tuber dry weight per plot. The best results occurred in the treatment of chicken manure growing media, while the lowest results occurred in the treatment without manure